Agroforestry in South Asia: Glimpses from Vedic to present times - Kumar, B. Mohan; Sikka, A. K. (Indian Farming, 2015)
During the Vedic period, the productive, protective, cultural, and spiritual aspects of trees and landscapes were underlined. Tree worshipping was prevalent in different parts of India, implying the conservation ethos of ancient Indian people. Traditionally, agroforestry is aimed at food production – either directly producing edible products or indirectly (facilitating enhanced and/ or sustained production). The produces from agroforestry are also sources of minerals and nutrients for improving household nutritional security especially for at-risk populations. In general, agroforestry is capable of making available diversified foodstuffs, averting malnutrition, and providing organic food materials, for which there is an emerging market even in the developing countries.